Pengaruh Kepemimpinan Kerja, Kompetensi Kerja, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Guru Wellington Intelligence School Medan - Rysanto, Rysanto; Hendry, Hendry; Wennoto, Stevi; Telaumbanua, Faudunasokhi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Wellington Intelligence School (WINS) is a national plus school established in 2013. WINS offers education from Toddler, Kindergarten, Primary School, to Junior High School and Senior High School. The school adopts the concept of multiple intelligences to help students recognize and maximize their potential, with the aim of developing hidden abilities that will support their future success. Currently, WINS is facing some internal issues. This study involved 57 people who made purchases at the company. The sampling technique used was a saturated sample, where the entire population was used as a research sample. The results showed a positive and significant influence partially between Leadership and Job Satisfaction, Job Competence and Job Satisfaction, and Work Environment and Job Satisfaction. Overall, Leadership, Job Competence, and Work Environment have a positive and significant influence on Job Satisfaction.